Inside the Mandapa of the Suhaveshwar Temple - Temples of India Project Team (Jio Institute, 2024)
This is a view of the south lateral transept inside the mandapa (pillared hall) of the Suhaveshwar Temple. The dwarf wall of the transept has an opening at the centre which leads to a small room. This style of the lateral wing or transept is similar to the mandapa of the Mahanaleshwar temple. The lower shafts of the pilasters embedded in these walls have elephant sculptures.